Diversity of medicinal plants from local traditions in Rokan Hulu District, Riau Province, Indonesia - DAHLIA DAHLIA; EVI SURYAWATI; ZULFARINA ZULFARINA; SRI WULANDARI (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Dahlia, Suryawati E, Zulfarina, Wulandari S. 2026. Diversity of medicinal plants from local traditions in Rokan Hulu District, Riau Province, Indonesia. Biodiversitas 27 (6): d270624. https://doi.org/10.13057/biodiv/d270624. Plant diversity in Rokan Hulu has given rise to a rich body of local wisdom. This indigenous knowledge includes the use of plants as traditional medicines, a practice that has persisted into the present century. Local knowledge plays a crucial role in plant conservation; however, it remains poorly documented, leading to the gradual erosion of these cultural practices. This study aims to identify the diversity of medicinal plant species and their uses, as well as to calculate key ethnobotanical indices, including use value (UV), plant part value (PPV), and fidelity level (FL). A qualitative approach was employed to describe medicinal plant species, methods of preparation and use, plant parts utilized, and types of ailments treated. Quantitative methods were applied to assess the relative importance of medicinal plants. Semi-structured interviews were conducted with 210 respondents selected through snowball sampling. A total of 178 medicinal plant species belonging to 63 families were recorded, with Zingiberaceae contributing the highest number of species (14 species). Herbaceous plants dominated the recorded species (32.58%). The highest UV was recorded for Curcuma longa (0.786), while the highest FL was observed for Hibiscus × rosa-sinensis (91.7%). Leaves were the most frequently used plant part (49.95%), as they are generally more abundant than other organs. Decoction was the most common method of preparation (50.6%), as local communities believe that boiling facilitates faster extraction of bioactive compounds and provides a safer preparation by eliminating pathogens. Oral administration (drinking) was the most prevalent mode of use (61.3%), as it is considered to enhance the absorption of active compounds by the body and is easier to apply.